Performance Evaluation of PPP-BOTDA-Based Distributed Optical Fiber Sensors - Hao Zhang; Zhishen Wu (International Journal of Distributed Sensor Networks)
The basic sensing behaviors of Pulse-Prepump Brillouin Optical Time Domain Analysis- (PPP-BOTDA-) based distributed fiber optic sensors (DFOSs) with a spatial resolution on the order of 0.1 m are first experimentally studied. Second, the sensing results for different types of optical fibres are compared. Based on these investigations, the performance of PPP-BOTDA—based DFOSs for crack monitoring is evaluated. The experimental results show that in the interior of an optical fibre, slippage between the bare fiber and the coating materials occurs and that different types of optical fibres have different degrees of slippage. Point fixation bonding methods can produce effective and correct measurement results when the gauge length of the optical fibre is longer than the critical effective sensing length (CESL), whereas the overall bonding method is still not feasible for monitoring localized deformation quantitatively. Finally, the differences between Brillouin Optical Time Domain Reflectometry (BOTDR) and BOTDA are discussed.